A Re-Examination of the Inflation Growth Relationship in the African Countries - Djiogap, Constant Fouopi (DEMO, 2018)
This paper returns on the non-linearity of the inflation - growth relationship. He estimates the role of the institutional quality appreciated by the independence of the central bank on the non-linearity of the inflation-growth relationship and identifies the optimal inflation rate in the African countries. In this respect, a panel of 53 African countries over the period 1980-2013 is used to make an analysis of regression of panel with progressive threshold (Panel Smooth Threshold Regression: PSTR developed by Gonzalez and al. 2005). A test of robustness is made with the method of moments generalized in system (GMM). Our results confirm the non-linearity of the relation inflation-growth. This non-linearity of the inflation growth relationship is conditioned by the quality of institutions. Countries with a higher quality of institutions experience less severe effects of inflation than countries having a lower quality of institutions. The optimal inflation rate for the African countries depends on the exchange regime. This rate diverges with those found for developed countries as well as for those of many developing countries.(original abstract)
Keywords: Inflation; Economic growth; Inflation rates; Institutions